IMPACT OF HIV ON FERTILITY IN NAÏVE PREMENOPAUSAL FEMALES - Okezie , Chukwuemeka Samuel; Aniebonam, Oluchi Mary (Global Journal of Medical and Health Science, 2024)
This study investigates the fertility status of naïve HIV-infected females of childbearing age. Approved by the Medical Ethical Committee of the University of Nigeria Teaching Hospital (UNTH), Enugu, and with informed consent obtained from all participants, the study involved 80 HIV-positive females aged 20 to 35 years from the PEPFAR HIV clinic at UNTH, Enugu. A control group of 80 age-matched, HIV-negative females was also included. Blood samples were collected and analyzed using standard methods. HIV diagnosis was confirmed through the WHO HIV test algorithm. Flow cytometry was utilized for CD4+ T lymphocyte enumeration, while hormone levels were assessed using competitive ELISA. Results indicated that serum oestradiol and progesterone levels in HIV-positive patients were significantly lower (p < 0.001) compared to the control group. However, in patients with CD4 counts ≥ 500 cells/µl, hormone levels did not significantly differ from controls (p > 0.05). Additionally, the CD4 count in HIV-positive patients was significantly reduced compared to the control group (p < 0.001). Intra-batch variations for oestradiol and progesterone were 0.53% and 1.30%, respectively, while inter-batch variations were 1.40% and 6.8%. These findings suggest that while HIV infection is associated with lower hormone levels, high CD4 counts may mitigate some effects on fertility